Metabolic and perceptual responses during spinning(R) cycle exercise - Kang, J.; Chaloupka, E. C.; Mastrangelo, M. A.; Hoffman, J. R.; Ratamess, N. A.; O'Connor, E. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The present investigation was undertaken to compare metabolic and perceptual responses between exercise performed at constant intensity (CON) and with a Spinning(R) protocol of variable intensity (VAR).